5G Networks: Challenges and Techniques for Energy Efficiency - Azhar, M.; Shabbir, A. (Engineering, Technology & Applied Science Research, 2018)
The growing importance of energy efficient networks with high data rate requirements is a major concern for network operators. Services provided by the network operators are required to ensure the consumers’ satisfaction. For the providing of high data rates with good signal quality, small cells are deployed. But these cells can increase energy consumption if not equipped with some intelligent power saving or distribution mechanism. In this paper, a previously tested small cell sleeping mode scheme is compared with the new proposed scheme of reducing power in low or normal traffic hours. This scheme provided 13-15% increase in energy efficiency. The new scheme resulted to beneficial simulated outcomes and can be applied to overcome the energy consumption issue.